7th Forum on New Materials - Part D 2016
DOI: 10.4028/www.scientific.net/ast.100.187
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Design and Manufacturing of Anti-Erosion Functional Surfaces Inspired from Desert Scorpion

Abstract: Sand erosion is a phenomenon that solid particles impinging to a wall cause serious mechanical damages to its surface. It's tough to be a machine in the desert: particles of dirt and sand work their way into moving parts, where they abrade helicopter propellers, airplane rotor blades, pipes and other equipments. However, the desert scorpion (Androctonus australis) live their entire lives subjected to blowing sand, yet they never appear to be eroded. In this study, the anti–erosion characteristic rules of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Inspired by the back of the desert scorpion, a few researchers have reported a hexagonal pit structure with excellent anti-erosion properties [186,[188][189][190]. The biomimetic samples with microstructures as shown in Figure 12d resulted in reduced erosion wear due to reduced solid particle velocity caused by rotational low velocity (explained in Figure 12f).…”
Section: Bioinspired Surfaces For Erosive Wear Resistancementioning
confidence: 99%
“…Inspired by the back of the desert scorpion, a few researchers have reported a hexagonal pit structure with excellent anti-erosion properties [186,[188][189][190]. The biomimetic samples with microstructures as shown in Figure 12d resulted in reduced erosion wear due to reduced solid particle velocity caused by rotational low velocity (explained in Figure 12f).…”
Section: Bioinspired Surfaces For Erosive Wear Resistancementioning
confidence: 99%
“…Hang and Zang et al [ 91 , 136 , 139 ] identified the anti-erosion functionality of the scorpion’s back and the outcomes of multi-coupling effects. Few research studies identified that surface morphology is one of the most critical factors in resisting erosion, i.e., the scorpion resists erosion without causing damage due to its surface morphology [ 136 , 140 , 141 , 142 ]. In some of the research studies, it was obtained that the scorpion body has a special arrangement of grooves on the back (evolution and adaptability to the living environment) that can alter the boundary layer flow over the surface and helps in resisting erosion [ 143 , 144 ].…”
Section: Biomimetic Surfaces Inspired By Animalsmentioning
confidence: 99%
“…Compared with the mold, the bionic non-smooth coupling treatment significantly improves the surface hardness, wear resistance and thermal fatigue performance of the mold. Han et al [ 24 , 25 ] the design and manufacture method of the bionic functional surface of a scorpion is proposed to improve the corrosion resistance of parts in environments with dust and sand. Tillmann et al [ 26 ] the honeycomb-like functional surface structure of an imitation scarab beetle head was processed by laser micro-processing technology.…”
Section: Introductionmentioning
confidence: 99%